LITERASI PENDEWASAAN USIA PERKAWINAN DAN HAK-HAK REPRODUKSI REMAJA - Widarini, N.P.; Subrata, M.; Adhi, K.T.; Suryadhi, M.A.H.; Ulandari, L.P.S. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
Cases of early marriage in Indonesia experienced an increase in the previous decades due to the COVID-19 pandemic. Reproductive health for adolescents has been mostly carried out in formal such as schools. STT as one of the traditional non-formal organizations needs to be targeted in reproductive health promotion. The purpose of community dedication is to increase literacy in reproductive health knowledge so as to bring positive changes to adolescents. The method of activity is education, discussion, questions and answers, role play, giving pre-post test questionnaires. The results of the activity showed changes in the knowledge, attitudes and intentions of adolescents after literacy was carried out. The increase in knowledge can be seen from the average post-test score of 6 which is higher than the average pre-test score of 5.32 (p=0.02). An increase in attitude can be seen from the average post-test score of 62.75, which is higher than the average pre-test score of 61.85 (p=0.03). The increase in the intention to mature at marriage age and use reproductive rights can be seen from the average post-test score of 13,20, which is higher than the average pre-test score of 12,82 (p=0.03). It is hoped that adolescents will get a good understanding so that they can go through their adolescents years without experiencing problems and become healthy and quality adolescents. Keywords: youth, maturing age at marriage, reproductive rights